Análisis bibliográfico de los textos fundamentales sobre la historia económica de España durante la Segunda República - Caruana de las Cagigas, Leonardo (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2018)
This article focuses on a number of authors of economic history who analyse the period from various perspectives: from global to sectorial analyses. Undoubtedly within the complexity of the global economic crisis of the 1930s, there was a clear lack of uniformity. Historians analysed the evolution of the peseta, foreign trade, fiscal policy, state debt and the “problems” of agrarian reform. Nonetheless there were also authors who conducted sectorial analyses. Finally, we review the most outstanding economists of the time who made their own assessments of the hardship from the perspective of a country undergoing its own industrial revolution.
Keywords: Second Republic; Economy; Economists